A versatile synthetic approach to various 5-alkynyl modified isatin derivatives: Cytotoxicity, acetylcholinesterase inhibition activity and molecular modeling study; Bioorganic Chemistry; Vol. 165 - Cheremnykh K. P. Kirill; Ivanov I. D. Igor; Hamad M. S. Mohammad; Khlebnikov A. I. Andrey Ivanovich; Savelyev V. A. Victor; Pokrovsky M. A. Mikhail; Pokrovsky A. G. Andrey; Shults E. E. Elvira Eduardovna (2025, 2025)
Title screen